Correction: A colorimetric and far-red fluorescent probe for the highly sensitive detection of silver(i). Issue 6 (16th January 2018) - Wang, Yong-jun; Liu, Jing-gong; Tan, Hui-ya; Yan, Jin-wu; Zhang, Lei
Abstract : Correction for 'A colorimetric and far-red fluorescent probe for the highly sensitive detection of silver(i )' by Yong-jun Wang et al., RSC Adv., 2017, 7, 55567–55570.